2022
DOI: 10.3389/fsurg.2022.1009448
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and mid-term effects of thoracoscopic repair of esophageal atresia: No anastomotic leaks or conversions to open technique

Abstract: The frequency rate of esophageal anastomosis leaks after thoracoscopic correction of esophageal atresia (EA) in the current literature is reported as 5.6%–24.7% and a conversion rate of 2%–53%. The objective of this retrospective study was to examine the characteristics of EA and analysis of the safety and efficacy of EA repair with the use of the thoracoscopic approach in a single academic center, as well as risk factors analysis in the context of short-term and mid-term follow-up status. A retrospective anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Preoperative ventilator dependence is an additional prognostic factor independent of the associated anomalies. These factors may have a more significant impact on survival than body weight [20]. In our study, 25% of cases needed mechanical ventilation before operation.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Preoperative ventilator dependence is an additional prognostic factor independent of the associated anomalies. These factors may have a more significant impact on survival than body weight [20]. In our study, 25% of cases needed mechanical ventilation before operation.…”
Section: Discussionmentioning
confidence: 62%
“…The literature review conducted by Okuyama et al [10] reported an anastomotic leakage rate ranging from 0 to 20%. A variety of factors can contribute to the leakage, such as excessive mobilization of the distal end of the esophagus, esophageal injury, poor suturing technique, anastomotic tension, the use of inappropriate sutures, associated ischemia, a long gap length or sepsis [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of patients with oesophageal atresia with CHD are usually treated by thoracotomy [10], but in this instance it was possible to treat it with thoracoscopy [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Esta última modalidad es la más utilizada en la actualidad a nivel global por las ventajas que aporta tanto para el paciente como para el cirujano: permite una amplia visualización del campo quirúrgico, elimina la morbilidad neonatal de la toracotomía tales como escoliosis, escápula alada, dolor crónico, debilidad del hombro, asimetría de la pared torácica; además, cabe destacar que permite lograr también resultados estéticos satisfactorios. (26) 4. CONCLUSIONES Los resultados en cuanto al abordaje y tratamiento de la atresia esofágica han mejorado considerablemente en las últimas décadas y en la actualidad la supervivencia a nivel mundial, sobre todo en países desarrollados, es del 90% e incluso superior en algunas regiones.…”
unclassified